2021
DOI: 10.1038/s41598-021-85165-x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of tau accumulation in prodromal Alzheimer’s disease using an ensemble machine learning approach

Abstract: We developed machine learning (ML) algorithms to predict abnormal tau accumulation among patients with prodromal AD. We recruited 64 patients with prodromal AD using the Alzheimer’s Disease Neuroimaging Initiative (ADNI) dataset. Supervised ML approaches based on the random forest (RF) and a gradient boosting machine (GBM) were used. The GBM resulted in an AUC of 0.61 (95% confidence interval [CI] 0.579–0.647) with clinical data (age, sex, years of education) and a higher AUC of 0.817 (95% CI 0.804–0.830) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Friedman [43] proposed the gradient boosting machine as a simple and highly flexible machine learning tool. It is a widely used machine learning algorithm that has been shown to be effective in a variety of applications [44][45][46]. The basic idea behind GBM is to build a prediction model using a set of poor learning algorithms, most commonly decision trees.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…Friedman [43] proposed the gradient boosting machine as a simple and highly flexible machine learning tool. It is a widely used machine learning algorithm that has been shown to be effective in a variety of applications [44][45][46]. The basic idea behind GBM is to build a prediction model using a set of poor learning algorithms, most commonly decision trees.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…However, recent findings suggested that tau pathology has more intimate links with ADrelated cognitive impairment than Aβ pathology, suggesting the tantalizing potential for clinical trials targeting tau [43,44]. A study classified 64 prodromal AD patients through GBM and RF algorithms [45]. A combination of demographic variables, MCI diagnosis information, NP test scores, APOE genotype, and cortical thickness resulted in the highest performance for GBM (AUC: 0.86) and RF (AUC: 0.82).…”
Section: Protein Biomarkers For Admentioning
confidence: 99%
“…Hence, the applications of machine learning in predicting the future course of dementia include: i) predicting if a patient with cognitive impairment patient will develop dementia [137], ii) predicting when the patient will reach a clinical dementia stage (i.e. duration of the prodromal disease phase) [86], and iii) predicting the progression of biomarkers such as cognition and MRI measurements [68,63].…”
Section: • Patient Outcomes After Treatment Ms Brain Cancer Strokementioning
confidence: 99%